Antegrade Double-J Stenting in Grossly Dilated and Tortuous Ureters - Shreshta, Manish Kiran; Narkhede, Amey; Gupta, Arun (Journal of Clinical Interventional Radiology ISVIR, 2020)
Failure of retrograde approach for ureteric stenting warrants percutaneous nephrostomy with antergrade stenting to relieve the pressure symptoms and prevent the need for external drainage. However, in some tight ureteric strictures with grossly dilated tortuous ureter it may not be possible to navigate a ureteric stent across. In such instances pull through or rendezvous techniques have been advocated. Here, we have illustrated simple and novel techniques for traversing tortuous ureters with tight strictures. In one instance, a guide wire was snared via the perurethral approach and the system stabilized from both ends; the flexometallic sheath was then advanced into the urinary bladder across the stricture and a ureteric stent was deployed. In the other situation where the ureter was very tortuous, plain twisting and turning maneuver with retraction of whole assembly was done to straighten the ureter followed by advancement of the flexometallic sheath and stationing of the ureteric stent. In both the cases no significant procedure-related complications were seen and patients were discharged in stable condition. Our experience has led us to believe that occasionally all facilities may not be accessible immediately or the desired armamentarium may be unavailable for interventional radiologists, especially when the patient is on the table; in such cases, simple improvisation and techniques can come in handy to place a ureteric stent across a dilated tortuous ureter.
Keywords: antegrade stenting; tortuous ureter; flexometallic sheath; perurethral approach